A syndromic surveillance tool to detect anomalous clusters of COVID-19 symptoms in the United States - Amparo Güemes; Soumyajit Ray; Khaled Aboumerhi; Michael R. Desjardins; Anton Kvit; Anne E. Corrigan; Brendan Fries; Timothy Shields; Robert D. Stevens; Frank C. Curriero; Ralph Etienne-Cummings (Scientific Reports, 2021)
Abstract Coronavirus SARS-COV-2 infections continue to spread across the world, yet effective large-scale disease detection and prediction remain limited. COVID Control: A Johns Hopkins University Study, is a novel syndromic surveillance approach, which collects body temperature and COVID-like illness (CLI) symptoms across the US using a smartphone app and applies spatio-temporal clustering techniques and cross-correlation analysis to create maps of abnormal symptomatology incidence that are made publicly available. The results of the cross-correlation analysis identify optimal temporal lags between symptoms and a range of COVID-19 outcomes, with new taste/smell loss showing the highest correlations. We also identified temporal clusters of change in taste/smell entries and confirmed COVID-19 incidence in Baltimore City and County. Further, we utilized an extended simulated dataset to showcase our analytics in Maryland. The resulting clusters can serve as indicators of emerging COVID-19 outbreaks, and support syndromic surveillance as an early warning system for disease prevention and control.